Gummy smile - causes and modern treatment methods - Blicharz, Monika; Blicharz, Agnieszka; Bartosik-Zielińska, Diana; Swatko, Tomasz; Bartosik, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Nowadays, patients come to doctors and dentists not only with pain complaints, but also to improve their appearance. Gummy smile, or overexposure of the gums when smiling, is one of the most common aesthetic problems they report. Gummy smile occurs primarily in young people and more often affects women. Brief description of the state of knowledge: A gummy smile is a condition in which a patient exposes more than 2 mm of gum during smiling. There are many causes of excessive gum exposure during smiling. These include gingival hypertrophy, hyperactive muscles, a disproportionately long upper lip, altered passive eruption, or excessive vertical growth of the jaw. Examination of the patient is aimed at determining the cause of the condition and choosing the appropriate treatment method. In cases of gingival hyperplasia and altered passive eruption, a gingivectomy or excision of part of the gingiva is used. Muscle hyperactivity is an indication for treatment with botulinum toxin or hyaluronic acid. The long lip can be treated with surgical methods, while vertical hypertrophy of the jaw requires orthodontic treatment or orthognathic surgery. Depending on the treatment method chosen, the patient’s appearance can change to varying degrees. The most striking changes are seen when orthognathic surgery is performed. Not only the patient’s smile is changed, but also the facial features. Summary: It is the doctor’s job to thoroughly examine the patient, make an appropriate diagnosis and choose the treatment method that will bring the best results. The multitude of treatment methods for gummy smiles allows them to be combined to achieve the best results. The choice of therapy should be based directly on the source of the problem. The patient should be informed about the course of treatment and possible side effects and take informed consent to the treatment.